Hello, I would be glad to help you with this:
a=(v-c)/t
at=v-c
-c=at-v
c=v-at
I hope this helps and good luck with the rest of your course work ,Please Please remember me for best answer
2006-11-09 15:51:37
·
answer #1
·
answered by Jaym 2
·
0⤊
0⤋
that is one of the things that a person must know about algebra
First, you are finding for c and it is inside the parenthesis with
a fraction, you must first simplify the fraction by multiplying both sides by variable t like this:
at = v - c
then transpose the variable v to the left because you are
looking for c
like this at - v = -c
the sign of the variable v will be negative if you transpose it .
then finally, divide both sides by negative 1 to make the variable
c be positive.
it will be -at +v =c arranging it to make the first term positive
the answer is v - at = c
hope you understand!
2006-11-12 08:35:25
·
answer #2
·
answered by jdash01 3
·
0⤊
0⤋
a=v-c/t
multipy oth sides by t
at=v-c
add c-at to both sides
then
c=v-at
2006-11-10 07:42:05
·
answer #3
·
answered by grandpa 4
·
0⤊
0⤋
multiplying by t
at=v-c
adding -v
at-v=-c
multiplying by-1
v-at=c
2006-11-09 23:57:12
·
answer #4
·
answered by raj 7
·
0⤊
0⤋
a=(v-c)/t
at=v-c
at-v=-c
-at+v=c
also written as v-at=c
2006-11-10 00:34:39
·
answer #5
·
answered by Raina 2
·
0⤊
0⤋
http://www.hostsrv.com/webmab/app1/MSP/quickmath/02/pageGenerate?site=quickmath&s1=equations&s2=solve&s3=basic
2006-11-09 23:45:51
·
answer #6
·
answered by hillbilly_coon 3
·
0⤊
0⤋
a = (v-c) / t
at = v - c
c = v - at
2006-11-09 23:45:22
·
answer #7
·
answered by novangelis 7
·
0⤊
0⤋
a=(v-c)/t
at=v-c
-c=at-v
c=v-at
2006-11-09 23:48:10
·
answer #8
·
answered by yupchagee 7
·
0⤊
0⤋
a*t=v-c
(a*t)-v=-c
v-(a*t)=c
2006-11-09 23:51:57
·
answer #9
·
answered by Mariposa 7
·
0⤊
0⤋